2007
DOI: 10.1038/sj.onc.1210801
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-coil domain containing 85B suppresses the β-catenin activity in a p53-dependent manner

Abstract: Aberrant accumulation of b-catenin is closely related to carcinogenesis. Mutations in the p53 gene are reported to induce the aberrant accumulation of b-catenin in the absence of dysfunction in the glycogen synthase kinase 3b (GSK3b)-mediated degradation pathway, but the mechanism remains incompletely understood. Here, we show that human coiled-coil domain containing 85B (CCDC85B) is induced by p53 and regulates b-catenin activity via interaction with the T-cell factor 4 in the nucleus. Moreover, CCDC85B enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Reportedly, CCDC85B suppressed the Wnt signaling pathway by inhibiting the interaction of β‐catenin with T‐cell factor 4 in the nucleus . To elucidate the mechanisms underlying CCDC85B‐induced proliferation and invasion of lung cancer cells, we investigated the Wnt signaling pathway.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Reportedly, CCDC85B suppressed the Wnt signaling pathway by inhibiting the interaction of β‐catenin with T‐cell factor 4 in the nucleus . To elucidate the mechanisms underlying CCDC85B‐induced proliferation and invasion of lung cancer cells, we investigated the Wnt signaling pathway.…”
Section: Resultssupporting
confidence: 50%
“…Du et al have found that CCDC85B interacts with p78/MCRS/MSP58 and has a role in the regulation of gene expression and cell proliferation. Furthermore, CCDC85B is also involved in Wnt signaling pathway by inhibiting the interaction of β‐catenin with the T‐cell factor 4 in the nucleus . These results indicated that CCDC85B might function in tumorigenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…The MAbs showed predominantly nuclear and cytoplasmic staining in most cell lines, which is consistent with previous reports. (12)(13)(14) Surprisingly some antibodies recognized DIPA at cell-cell junctions, which is unreported in the literature. MAbs 2G7 and 3E3 produced junctional staining patterns in MDCK cells.…”
Section: Immunofluorescencementioning
confidence: 90%
“…DIPA can endogenously regulate adipocyte differentiation by inhibiting C/EBP-b and C/EBP-g. (13) When induced by p53 activation, DIPA can compete with b-catenin for binding to the TCF4 transcription factor, which effectively down-regulates Wnt target gene expression. (14) Thus, DIPA is mostly found in the nucleus and appears to function primarily in transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation